(untitled) (Physical Education, Health and Social Sciences, 2025)
Large-scale renewable energy infrastructure projects are central to achieving global decarbonization objectives, yet their deployment remains constrained by financial risks that elevate capital costs and limit private investment. Although the levelized cost of electricity for solar and wind technologies has declined dramatically over the past decade, the financial structure of these projects continues to be shaped primarily by risk allocation rather than technology costs alone. This study examines how financial risk allocation mechanisms influence project bankability, weighted average cost of capital (WACC), debt capacity, and private capital mobilization in large-scale renewable energy projects. Using global investment data, institutional reports, and representative project finance modeling, the paper evaluates the financial implications of allocating construction, offtake, regulatory, grid, and market risks across public and private stakeholders. The analysis shows that projects supported by long-term, bankable power purchase agreements experience WACC reductions of approximately 150–350 basis points compared to merchant-exposed projects. Effective transfer of construction risk through fixed-price EPC contracts increases sustainable debt capacity by 7–12%, while public risk mitigation instruments such as partial risk guarantees increase private investment mobilization by 20–40% in higher-risk markets. The paper develops an integrated conceptual model linking risk allocation mechanisms to investor risk perception and financial outcomes. The findings highlight that optimizing financial risk allocation is a critical lever for accelerating renewable energy deployment, particularly in emerging economies, and that poorly designed risk-sharing frameworks can undermine investment even in cost-competitive markets.